Evolving Impact of COVID‐19 on Transplant Center Practices and Policies in the United States. Issue 12 (28th September 2020) - Boyarsky, Brian J.; Ruck, Jessica M.; Chiang, Teresa Po‐Yu; Werbel, William A.; Strauss, Alexandra T.; Getsin, Samantha N.; Jackson, Kyle R.; Kernodle, Amber B.; Van Pilsum Rasmussen, Sarah E.; Baker, Talia B.; Al Ammary, Fawaz; Durand, Christine M.; et al.
Abstract: In our first survey of transplant centers in March 2020, >75% of kidney and liver programs were either suspended or operating under restrictions. To safely resume transplantation, we must understand the evolving impact of COVID‐19 on transplant recipients and center‐level practices. We therefore conducted a six‐week follow‐up survey May 7‐15, 2020, and linked responses to the COVID‐19 incidence map, with a response rate of 84%. Suspension of live donor transplantation decreased from 72% in March to 30% in May for kidneys and from 68% to 52% for livers. Restrictions/suspension of deceased donor transplantation decreased from 84% to 58% for kidneys and from 73% to 42% for livers. Resuming transplantation at normal capacity was envisioned by 83% of programs by August 2020. Exclusively using local recovery teams for deceased donor procurement was reported by 28%. Respondents reported caring for a total of 1166 COVID‐19–positive transplant recipients; 25% were critically ill. Telemedicine challenges were reported by 81%. There was a lack of consensus regarding management of potential living donors or candidates with SARS‐CoV‐2. Our findings demonstrate persistent heterogeneity in center‐level response to COVID‐19 even as transplant activity resumes, making ongoing national data collection and real‐time analysis critical to inform best practices.